PVC pre-coating film and preparation method thereof

The PVC floor coating functionality is solved by using a PVC pre-coated film containing acrylic resin, amide monomer, hydroxy monomer, nanoalumina and Kevlan nanofiber-carbon nanotube composite materials on PVC floors. The problems of uneven gloss, poor adhesion and unscratch resistance during coating have achieved higher wear resistance and adhesion.

CN119432240APending Publication Date: 2025-02-14AIJI NEW MATERIALS TECHNOLOGY (WUXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411718405.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When applying functional coatings on composite-formed PVC floors, defects such as uneven gloss, poor adhesion, and unscratch resistance are prone to occur.

Method used

A PVC pre-coated film is used, which includes a PVC layer and a cured coating, which consists of a primer, an adhesive layer, a functional layer and a topcoat layer. The topcoat layer uses acrylic resin as the main resin, and amide monomer, hydroxy monomer, nanoalumina and Kevlan nanofiber-carbon nanotube composite materials are added therein to improve the wear resistance and adhesion of the topcoat.

Benefits of technology

By improving the wear resistance and adhesion of the topcoat layer, the pre-coated film obtains better scratch resistance and gloss uniformity, significantly improving the performance of the floor surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157427320000111
    Figure BDA0005157427320000111
Patent Text Reader

Abstract

The invention relates to the technical field of floor surface decoration materials, and particularly discloses a PVC pre-coating film and a preparation method thereof. The PVC pre-coating film comprises a PVC layer and a curing coating, the curing coating comprises a primer, a bonding layer, a functional layer and a finish paint layer, and the finish paint layer comprises the following materials in parts by weight: 30-40 parts of acrylic resin; 3-4 parts of an amide monomer; 1-2 parts of a hydroxyl monomer; 10 to 20 parts of filler; 30 to 50 parts of a solvent; 0.1 to 1 part of an initiator; the acrylic resin is trifunctional acrylic resin, the amide monomer is selected from hyperbranched polyamide or acrylamide, and the hydroxyl monomer is selected from 4-hydroxybutyl vinyl ether or 2-hydroxyethyl methacrylate phosphate. The PVC pre-coating film can be used in floors, and has the advantages of high wear resistance, high strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of floor surface decoration materials, and more specifically, to a PVC pre-coating film and a preparation method thereof. Background Art

[0002] PVC floor is a new type of lightweight floor decoration material that is very popular in the world today. It has the advantages of being green and environmentally friendly, extremely wear-resistant, with a wide variety of patterns and colors, and quick installation and construction. It has been widely used and highly recognized in places with large traffic, such as hospitals, schools, office buildings, shopping malls, supermarkets, and transportation. In actual use, in order to meet consumers' requirements for different performances of floor surface, such as wear resistance, scratch resistance, strength, and good feel, various functional coatings are often added to the floor surface to meet the needs of different consumers for different types of floor.

[0003] Currently, most multi-layer composite floors improve their performance by coating with functional coatings. However, coating functional coatings on laminated PVC floors is prone to defects such as uneven gloss, poor adhesion, and scratch resistance. Therefore, the coating material needs to be improved. Summary of the invention

[0004] In order to improve the limitations of the coating film, the present application provides a PVC pre-coating film and a preparation method thereof.

[0005] The present application provides a PVC pre-coated film, which adopts the following technical solution:

[0006] In a first aspect, the present application provides a PVC pre-coated film, comprising: a PVC layer and a cured coating, wherein the cured coating comprises a primer, an adhesive layer, a functional layer and a topcoat layer, and the topcoat layer comprises the following materials in parts by weight:

[0007] 30-40 parts of acrylic resin;

[0008] 3-4 parts of amide monomer;

[0009] 1-2 parts of hydroxyl monomer;

[0010] 10-20 parts of filler;

[0011] 30-50 parts of solvent;

[0012] Initiator 0.1-1 part;

[0013] The acrylic resin is a trifunctional acrylic resin, the amide monomer is selected from hyperbranched polyamide or acrylamide, and the hydroxyl monomer is selected from 4-hydroxybutyl vinyl ether or 2-hydroxyethyl methacrylate phosphate.

[0014] By adopting the above technical solution, acrylic resin is preferably used as the main resin. The acrylic resin structure can form hydrogen bonds between molecules, which can improve the interaction force and compactness between molecules, thereby improving the wear resistance of the topcoat layer. Trifunctional acrylic resin is preferred. As the number of functional groups increases, the crosslinking degree of the topcoat is increased to improve the wear resistance of the topcoat. The trifunctional acrylic resin can not only effectively improve the crosslinking degree of the topcoat, but also maintain a suitable viscosity, reduce the problems of bubbles or shrinkage of the topcoat, and stably and effectively improve the wear resistance of the topcoat, thereby enabling the pre-coated film to obtain a better scratch resistance.

[0015] Preferably, amide monomers and hydroxyl groups are added to the topcoat. The introduction of amide groups and hydroxyl groups can form hydrogen bonds in the topcoat, thereby increasing the crosslinking degree of the topcoat to further improve the wear resistance of the topcoat.

[0016] Optionally, the filler includes aluminum oxide, and the particle size of the aluminum oxide is 30-50 nm.

[0017] By adopting the above technical solution, nano-alumina is preferably used as filler. The high surface free energy of nano-alumina enables the nano-alumina to be evenly dispersed in the topcoat layer, so that the topcoat layer obtains excellent strength and wear resistance. The particle size of alumina is further optimized. At a suitable particle size, the distance between alumina and resin becomes smaller, thereby reducing the system gap, thereby improving the density and wear resistance of the topcoat.

[0018] Optionally, the filler also includes a Kevlar nanofiber-carbon nanotube composite material.

[0019] By adopting the above technical solution, since Kevlar nanofibers have the advantages of high strength, high modulus and high heat resistance, they can be added to the topcoat as a supporting material to stably improve the mechanical strength of the topcoat, and can form a network structure in the topcoat by interlacing, further improving the strength and wear resistance of the topcoat. When Kevlar nanofiber-carbon nanotube composite materials are added to the topcoat, since the hollow porous structure of carbon nanotubes is loaded on the surface of Kevlar nanofibers, the composite materials can form a multi-branched tree-like structure, effectively increasing the bonding effect between Kevlar nanofibers and the topcoat, and can also form a more complex network structure in the topcoat, stably improving the density of the topcoat.

[0020] Optionally, the Kevlar nanofiber-carbon nanotube composite material is prepared as follows: Kevlar nanofiber is immersed in a suspension of carbon nanotubes and polyaniline, the mixture is immersed, filtered, and dried to prepare the composite material.

[0021] By adopting the above technical solution, polyaniline is introduced in the reaction process. Under the initiation of polyaniline, carbon nanotubes can be loaded on the surface of Kevlar nanofibers by self-assembly, so that the composite material forms a multi-branched tree-like structure.

[0022] Optionally, the Kevlar nanofiber-carbon nanotube composite material is a composite material modified by a modifier, and the modifier includes polytetrafluoroethylene wax.

[0023] By adopting the above technical solution, it is preferred to use polytetrafluoroethylene wax to modify the composite material. Since the hollow structure of the carbon nanotubes and the multi-branched tree-like structure of the composite material can both load part of the polytetrafluoroethylene wax, the polytetrafluoroethylene wax has a relatively good lubricating effect, which can not only improve the bonding effect between the composite material and the topcoat, but also form a continuous transfer film on the surface of the topcoat to improve the lubricity of the topcoat surface, thereby effectively improving the wear resistance of the topcoat. And by using the hollow structure of the carbon nanotubes to load the polytetrafluoroethylene wax, the polytetrafluoroethylene wax can be slowly overflowed, that is, the lubrication time of the polytetrafluoroethylene wax on the topcoat is extended, that is, the wear resistance time of the topcoat is extended.

[0024] Optionally, the modification treatment includes the following steps: mixing polytetrafluoroethylene wax with a binder to obtain a mixture, impregnating the Kevlar nanofiber-carbon nanotube composite material into the mixture, stirring, filtering, and drying to obtain a modified composite material.

[0025] Optionally, the filler also includes molybdenum disulfide.

[0026] By adopting the above technical solution, preferably using molybdenum disulfide as a filler, the sheet material of molybdenum disulfide is added to the topcoat, which can form a continuous overlapping wear-resistant layer on the surface of the topcoat, thereby effectively improving the wear resistance of the topcoat. In addition, molybdenum disulfide can cooperate with nano-alumina, and the nano-alumina can be dispersed and loaded on the surface of molybdenum disulfide to improve the dispersion effect of nano-alumina in the topcoat, and can form a one-dimensional-two-dimensional composite structure of particles-sheets, which synergistically improves the mechanical strength and wear resistance of the topcoat.

[0027] Optionally, the molybdenum disulfide is molybdenum disulfide modified with a silane coupling agent.

[0028] By adopting the above technical scheme, it is preferred to use a silane coupling agent to modify molybdenum disulfide. The introduction of the silane coupling agent can reduce the stacking phenomenon of molybdenum disulfide in the topcoat, can evenly overlap in the topcoat to form a shielding layer, and can effectively load nano-alumina to improve the dispersion uniformity of nano-alumina, further improve the dispersion uniformity of the filler in the topcoat, so as to stably improve the wear resistance of the topcoat.

[0029] Optionally, the primer layer includes acrylic resin, chlorowax resin, solvent and initiator, and the bonding layer includes acrylic resin, acrylate, acrylate monomer and initiator.

[0030] By adopting the above technical solution, the primer layer, the bonding layer and the topcoat layer all use acrylic resin as the main material, which can greatly improve the bonding effect between the primer layer, the bonding layer and the topcoat layer, that is, the pre-coating film obtains excellent integrity.

[0031] In a second aspect, the present application provides a method for preparing a PVC pre-coated film, using the following technical solution:

[0032] A method for preparing a PVC pre-coating film comprises the following steps:

[0033] S1. Raw material preparation: The raw materials for preparing the adhesive primer layer and the bonding layer are respectively stirred evenly with a dispersion kettle to obtain a finished paint product;

[0034] S2, primer coating: evenly apply the adhesion primer layer on the surface of the PVC transparent film layer with a roller coater;

[0035] S3, adhesive layer coating: evenly apply the adhesive layer on the surface of the attached primer layer with a roller coater, and perform LED-UV curing;

[0036] S4, functional layer coating: evenly coat the functional layer on the surface of the bonding layer with a roller coater, and perform LED-UV curing;

[0037] S5. Topcoat coating: Apply topcoat coating on the surface of the functional layer and perform radiation curing to obtain a PVC pre-coating film.

[0038] In summary, this application has the following beneficial effects:

[0039] 1. Since the present application preferably uses acrylic resin as the main resin, the acrylic resin structure has urethane bonds, which can form hydrogen bonds between molecules, and can improve the interaction force and compactness between molecules, thereby improving the wear resistance of the topcoat layer. Trifunctional acrylic resin is preferred. As the number of functional groups increases, the crosslinking degree of the topcoat is improved to improve the wear resistance of the topcoat. The trifunctional acrylic resin can not only effectively improve the crosslinking degree of the topcoat, but also maintain a suitable viscosity, reduce the problems of bubbles or shrinkage of the topcoat, and stably and effectively improve the wear resistance of the topcoat, thereby enabling the pre-coated film to obtain a better scratch resistance. It is preferred to add amide monomers and hydroxyl groups to the topcoat. The introduction of amide groups and hydroxyl groups can form hydrogen bonds in the topcoat, thereby increasing the crosslinking degree of the topcoat to further improve the wear resistance of the topcoat.

[0040] 2. In this application, Kevlar nanofibers have the advantages of high strength, high modulus and high heat resistance, and are added to the topcoat as a supporting material to stably improve the mechanical strength of the topcoat, and can form a network structure in the topcoat by interlacing, further improving the strength and wear resistance of the topcoat. When Kevlar nanofiber-carbon nanotube composite materials are added to the topcoat, the hollow porous structure of the carbon nanotubes is loaded on the surface of the Kevlar nanofibers, so that the composite materials can form a multi-branched tree-like structure, effectively increasing the bonding effect between the Kevlar nanofibers and the topcoat, and can also form a more complex network structure in the topcoat, stably improving the density of the topcoat.

[0041] 3. In this application, polytetrafluoroethylene wax is preferably used to modify the composite material. Since the hollow structure of the carbon nanotubes and the multi-branched tree-like structure of the composite material can both load part of the polytetrafluoroethylene wax, the polytetrafluoroethylene wax has a relatively good lubricating effect, which can not only improve the bonding effect between the composite material and the topcoat, but also form a continuous transfer film on the surface of the topcoat to improve the lubricity of the topcoat surface, thereby effectively improving the wear resistance of the topcoat. And by using the hollow structure of the carbon nanotubes to load the polytetrafluoroethylene wax, the polytetrafluoroethylene wax can be slowly overflowed, that is, the lubrication time of the polytetrafluoroethylene wax on the topcoat is extended, that is, the wear resistance time of the topcoat is extended. DETAILED DESCRIPTION

[0042] The present application is further described in detail below with reference to the embodiments.

[0043] Preparation Example

[0044] Preparation example of Kevlar nanofiber-carbon nanotube composite material

[0045] Preparation Example 1

[0046] 0.2 g of carbon nanotubes were immersed in a mixed acid solution of 30 mL of concentrated nitric acid and 90 mL of concentrated sulfuric acid. After 4 h, the mixture was washed and dialyzed for 24 h to obtain modified carbon nanotubes. The modified carbon nanotubes were prepared with 1 mg / mL of ammonium dodecylbenzenesulfonate to obtain a 0.2 mg / mL carbon nanotube solution. After ultrasonic treatment, 0.04 mg / mL of polyaniline was added and stirred to obtain a composite suspension.

[0047] The Kevlar nanofiber is immersed in a composite suspension of carbon nanotubes and polyaniline, and the composite material is prepared by immersion treatment, filtering and drying.

[0048] Preparation Example 2

[0049] 0.2 g of carbon nanotubes were immersed in a mixed acid solution of 30 mL of concentrated nitric acid and 90 mL of concentrated sulfuric acid. After 4 h, the mixture was washed and dialyzed for 24 h to obtain modified carbon nanotubes. The modified carbon nanotubes were prepared with 1 mg / mL of ammonium dodecylbenzenesulfonate to obtain a 0.2 mg / mL carbon nanotube solution. After ultrasonic treatment, 0.04 mg / mL of polyaniline was added and stirred to obtain a composite suspension.

[0050] The Kevlar nanofiber is treated with oxygen plasma to obtain modified Kevlar nanofiber.

[0051] The modified Kevlar nanofiber is immersed in a composite suspension of carbon nanotubes and polyaniline, subjected to an immersion treatment, filtered, and dried to prepare a composite material.

[0052] Preparation Example 3

[0053] The polytetrafluoroethylene wax and the binder (epoxy resin) are mixed to obtain a mixture with a mass fraction of 15%, the Kevlar nanofiber-carbon nanotube composite material is impregnated into the mixture, stirred, filtered, and dried to obtain a modified composite material.

[0054] Preparation Example 4

[0055] The silane coupling agent KH550 was dissolved in an ethanol solution (anhydrous ethanol: water = 1:1) for hydrolysis, the pH was adjusted to 4-5, and stirred for 2 hours to obtain a modified liquid. Molybdenum disulfide was dispersed in the solution, stirred at 70°C for 4 hours, washed, dried, and ground to obtain modified molybdenum disulfide.

[0056] Example

[0057] Examples 1-3

[0058] On the one hand, the present application provides a PVC pre-coated film, comprising a PVC layer and a cured coating, wherein the cured coating comprises a primer, a bonding layer, a functional layer and a topcoat layer, and the topcoat layer comprises the following materials: acrylic resin, amide monomer, hydroxyl monomer, filler, solvent and initiator, and the specific weight parts are shown in the table below.

[0059] Wherein, the acrylic resin is a trifunctional acrylic resin (industrial grade), the amide monomer can be acrylamide or hyperbranched polyamide, and in this embodiment, the amide monomer is selected from hyperbranched polyamide (industrial grade); the hydroxyl monomer can be 4-hydroxybutyl vinyl ether or 2-hydroxyethyl methacrylate phosphate, and in this embodiment, the hydroxyl monomer is selected from 4-hydroxybutyl vinyl ether (99.9%). The filler includes 30nm alumina, the solvent is butyl acetate, and the initiator is TPO.

[0060] The primer includes 6kg of difunctional polyurethane acrylate resin, 3kg of chloroacetic acid resin, 35kg of difunctional polyurethane acrylate monomer, 40kg of butyl acetate and 0.5kg of TPO.

[0061] The adhesive layer includes 45 kg of difunctional polyurethane acrylate resin, 30 kg of 1,6-hexanediol diacrylate, 13 kg of isobornyl acrylate and 3 kg of TPO.

[0062] Matte primer is used for the functional layer.

[0063] On the other hand, the present application provides a method for preparing a PVC pre-coated film, comprising the following steps:

[0064] S1. Raw material preparation: The raw materials for preparing the adhesive primer layer and the bonding layer are respectively stirred evenly with a dispersion kettle to obtain a finished paint product;

[0065] S2. Primer coating: Use a roller coater to evenly coat the adhesive primer layer on the surface of the PVC transparent film layer. The coating amount of the primer layer is 12g / m 2 .

[0066] S3, adhesive layer coating: the adhesive layer is evenly coated on the surface of the attached primer layer with a roller coater, and LED-UV curing is performed. The coating amount of the adhesive layer is 12g / m 2 .

[0067] S4. Functional layer coating: Use a roller coater to evenly coat the functional layer on the surface of the bonding layer and perform LED-UV curing. The coating amount of the functional layer is 12g / m 2 .

[0068] S5. Topcoat coating: Topcoat the functional layer with a coating weight of 12g / m 2 , and radiation curing is performed to obtain a PVC pre-coated film.

[0069] Table 1 Composition of Examples 1-3

[0070] Weight / kg Example 1 Example 2 Example 3 Acrylic resin 30 35 40 Amide monomer 3 3.5 4 Hydroxyl monomer 1 1.5 2 filler 10 15 20 Solvents 30 40 50 Initiator 0.1 0.5 1

[0071] Example 4

[0072] The difference from Example 2 is that the filler includes the composite material prepared in Preparation Example 1 and nano-alumina with a particle size of 30 nm in a mass ratio of 1:1, which replaces the nano-alumina in Example 2 to prepare the topcoat layer.

[0073] Example 5

[0074] The difference from Example 2 is that the filler includes Kevlar nanofibers and nano-alumina with a mass ratio of 1:1, which replace the nano-alumina in Example 2 to prepare the topcoat layer.

[0075] Example 6

[0076] The difference from Example 2 is that the filler includes the composite material prepared in Preparation Example 2 and nano-alumina with a particle size of 30 nm in a mass ratio of 1:1, which replaces the nano-alumina in Example 2 to prepare the topcoat layer.

[0077] Example 7

[0078] The difference from Example 2 is that the filler includes the composite material prepared in Preparation Example 3 and nano-alumina with a particle size of 30 nm in a mass ratio of 1:1, which replaces the nano-alumina in Example 2 to prepare the topcoat layer.

[0079] Example 8

[0080] The difference from Example 2 is that the filler includes the composite material prepared in Preparation Example 3 in a mass ratio of 1:1:1, nano-alumina with a particle size of 30 nm and molybdenum disulfide, which replaces the nano-alumina in Example 2 to prepare the topcoat layer.

[0081] Example 9

[0082] The difference from Example 2 is that the filler includes the composite material prepared in Preparation Example 3 in a mass ratio of 1:1:1, nano-alumina with a particle size of 30 nm, and modified molybdenum disulfide prepared in Preparation Example 4, instead of the nano-alumina in Example 2, to prepare the topcoat layer.

[0083] Comparative Example

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 2 is that in this comparative example, difunctional polyurethane acrylate is used to replace the trifunctional acrylate in Example 2 to prepare the topcoat layer.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 2 is that in this comparative example, no amino monomer is added to prepare the topcoat layer.

[0088] Performance testing

[0089] The pre-coated film and SPC substrate were heated to 175°C, pressed by a steel roller for 5 seconds, cooled and formed, and then the performance test was performed.

[0090] (1) Wear resistance test: According to the standard GB / T 1768-2006, the wear value of the pre-coated film is tested using a V-type abrasion tester.

[0091] (2) Hardness test: Test the hardness of the pre-coated film according to "GB / T 6739-2006 Paint and varnish pencil method for determination of paint film hardness";

[0092] (3) Adhesion test: Test the adhesion of the pre-coated film according to ASTM D3359.

[0093] Table 2 Performance test

[0094]

[0095] Combining the performance test comparison in Table 2, we can find that:

[0096] After testing, the adhesion of the pre-coating film of Examples 1-9 was 5B, and the adhesion of the pre-coating film of Comparative Examples 1-2 was 4B.

[0097] After 12 days of use, the wear resistance of the pre-coated film prepared in Example 7 was tested, and the abrasion loss was 30 mg / 100 r, which still maintained a good wear resistance effect, that is, it could play a long-term wear resistance effect.

[0098] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the wear resistance and hardness of the pre-coated film prepared in Examples 1-3 are improved. This shows that in the present application, the trifunctional acrylic resin increases the cross-linking degree of the topcoat as the number of functional groups increases, so as to improve the wear resistance of the topcoat. The trifunctional acrylic resin can not only effectively improve the cross-linking degree of the topcoat, but also maintain a suitable viscosity, reduce the problems of bubbles or shrinkage of the topcoat, and stably and effectively improve the wear resistance of the topcoat, thereby enabling the pre-coated film to obtain a better scratch resistance. Amide monomers and hydroxyl groups are added to the topcoat. The introduction of amide groups and hydroxyl groups can form hydrogen bonds in the topcoat, thereby increasing the cross-linking degree of the topcoat to further improve the wear resistance of the topcoat. The particle size of alumina is optimized. At a suitable particle size, the distance between alumina and the resin becomes smaller, thereby reducing the system gap, thereby improving the density and wear resistance of the topcoat.

[0099] 2. By comparing Examples 4-6 with Example 2, it can be found that the wear resistance, hardness and adhesion of the pre-coated films prepared in Examples 4-6 are all improved, which shows that the Kevlar nanofibers in this application have the advantages of high strength, high modulus and high heat resistance, and can be added to the topcoat as a supporting material to stably improve the mechanical strength of the topcoat, and can form a network structure in the topcoat by interlacing, further improving the strength and wear resistance of the topcoat. The Kevlar nanofiber-carbon nanotube composite material, because the hollow porous structure of the carbon nanotubes is loaded on the surface of the Kevlar nanofibers, can make the composite material form a multi-branched tree-like structure, effectively increasing the bonding effect between the Kevlar nanofibers and the topcoat, and can also form a more complex network structure in the topcoat, stably improving the density of the topcoat.

[0100] 3. By comparing Example 7 with Example 2, it can be found that the wear resistance of the pre-coating film prepared in Example 7 is improved, which shows that in this application, polytetrafluoroethylene wax is used to modify the composite material. Since the hollow structure of the carbon nanotubes and the multi-branched tree-like structure of the composite material can both load part of the polytetrafluoroethylene wax, the polytetrafluoroethylene wax has a relatively good lubricating effect, which can not only improve the bonding effect between the composite material and the topcoat, but also form a continuous transfer film on the surface of the topcoat to improve the lubricity of the topcoat surface, thereby effectively improving the wear resistance of the topcoat. And by using the hollow structure of the carbon nanotubes to load the polytetrafluoroethylene wax, the polytetrafluoroethylene wax can be slowly overflowed, that is, the lubrication time of the polytetrafluoroethylene wax on the topcoat is extended, that is, the wear resistance time of the topcoat is extended.

[0101] 4. By comparing Examples 8-9 with Example 2, it can be found that the wear resistance and hardness of the pre-coated film prepared in Examples 8-9 are improved, which shows that molybdenum disulfide is used as a filler in this application, and molybdenum disulfide can cooperate with nano-alumina, and nano-alumina can be dispersed and loaded on the surface of molybdenum disulfide to form a one-dimensional-two-dimensional composite structure of particles-sheets, which synergistically improves the mechanical strength and wear resistance of the topcoat. Molybdenum disulfide is modified by a silane coupling agent to improve the dispersibility of molybdenum disulfide, and molybdenum disulfide can be combined with amide monomers. Due to the introduction of epoxy groups in the composite material, molybdenum disulfide can be combined with Kevlar nanofiber-carbon nanotube composite material loaded with polytetrafluoroethylene wax, thereby forming a one-dimensional-two-dimensional-three-dimensional multiple composite structure, which can effectively improve the density and wear resistance of the topcoat.

[0102] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A PVC pre-coated film, characterized in that: include: PVC layer and cured coating, the cured coating comprises a primer, a bonding layer, a functional layer and a topcoat layer, and the topcoat layer comprises the following materials in parts by weight: 30-40 parts of acrylic resin; 3-4 parts of amide monomer; 1-2 parts of hydroxyl monomer; 10-20 parts of filler; 30-50 parts of solvent; Initiator 0.1-1 part; The acrylic resin is a trifunctional acrylic resin, the amide monomer is selected from hyperbranched polyamide or acrylamide, and the hydroxyl monomer is selected from 4-hydroxybutyl vinyl ether or 2-hydroxyethyl methacrylate phosphate.

2. A PVC pre-coated film according to claim 1, characterized in that: The filler comprises aluminum oxide, and the particle size of the aluminum oxide is 30-50 nm.

3. A PVC pre-coated film according to claim 2, characterized in that: The filler also includes a Kevlar nanofiber-carbon nanotube composite material.

4. A PVC pre-coated film according to claim 3, characterized in that: The preparation of the Kevlar nanofiber-carbon nanotube composite material is as follows: Kevlar nanofiber is immersed in a suspension of carbon nanotubes and polyaniline, and the mixture is immersed, filtered, and dried to prepare the composite material.

5. A PVC pre-coated film according to claim 3, characterized in that: The Kevlar nanofiber-carbon nanotube composite material is a composite material modified by a modifier, and the modifier includes polytetrafluoroethylene wax.

6. A PVC pre-coated film according to claim 5, characterized in that: The modification treatment comprises the following steps: mixing polytetrafluoroethylene wax with a binder to obtain a mixture, impregnating the Kevlar nanofiber-carbon nanotube composite material into the mixture, stirring, filtering, and drying to obtain a modified composite material.

7. A PVC pre-coated film according to claim 2, characterized in that: The filler also includes molybdenum disulfide.

8. A PVC pre-coated film according to claim 7, characterized in that: The molybdenum disulfide is molybdenum disulfide modified by a silane coupling agent.

9. A PVC pre-coated film according to claim 1, characterized in that: The primer layer comprises acrylic resin, chlorowax resin, solvent and initiator, and the bonding layer comprises acrylic resin, acrylate, acrylate monomer and initiator.

10. The method for preparing a PVC pre-coating film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Raw material preparation: The raw materials for preparing the adhesive primer layer and the bonding layer are respectively stirred evenly with a dispersion kettle to obtain a finished paint product; S2, primer coating: evenly apply the adhesion primer layer on the surface of the PVC transparent film layer with a roller coater; S3, adhesive layer coating: evenly apply the adhesive layer on the surface of the attached primer layer with a roller coater, and perform LED-UV curing; S4, functional layer coating: evenly coat the functional layer on the surface of the bonding layer with a roller coater, and perform LED-UV curing; S5. Topcoat coating: Apply topcoat coating on the surface of the functional layer and perform radiation curing to obtain a PVC pre-coating film.